Exploration of characteristics of trichomes, chlorophyl content, and lead content in Fabaceae leaves in the Malabar Urban Forest, Malang - Latifa, Roimil; Hadi, Samsun; Nurrohman, Endrik (Universitas Islam Negeri Sumatera Utara, 2024)
This research aimed to analyze the characteristics of trichomes, chlorophyll and lead content of various leaves in the Fabaceae family in the Malabar Urban Forest, Malang. The research was carried out using direct exploration methods (for sampling the leaves of each plant), and laboratory observations. The research will start from July 2023 to May 2024. The research was carried out in the Malabar Urban Forest, Malang, and the Biology Laboratory of UMM. Observation of anatomical structures using a binocular microscope, leaf chlorophyll content using a spectrophotometer, and lead content using the AAS method. The results of the research show that [1] there are variations in the characteristics of leaf trichomes in terms of type and other characteristics and there are variations in the number or average of trichomes; [2] Chlorophyll content in various types of leaves of the Fabaceae family in the Malabar Urban Forest. The highest chlorophyll a and b content is found in the Samanea saman plant and the lowest in Erythrina crista-galli; and [3] leaf lead content shows variation. The highest lead content is in the leaves of the Samanea saman plant and the lowest is Gliricidia sepium and Senna siamea. This research provides implications as baseline data for monitoring changes in trichome characteristics, chlorophyll content and lead in the leaves of Fabaceae family plants in the Malabar Urban Forest in the future as indicators of environmental dynamics. Information regarding variations in Fabaceae leaf characteristics can be used to develop bioindicators of environmental pollution, especially related to heavy metal pollution, as well as provide input for the management and conservation of urban forests.